2021
DOI: 10.31235/osf.io/np28g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“My daughter is not like that”: A qualitative study of parental perception on child sexual abuse risk

Abstract: The aim of this study was to explore parental beliefs on the risk of CSA, specifically victim- and perpetrator-specific risk of child sexual abuse to their children, as well as parents' approaches to protecting their children. Data were collected from 22 parents during focus group interviews (n=6) combined with activity-oriented questions. Based on data, four perpetrator and two victim-specific risk profiles were created. When parents find similarities between their children and perceived victims or perpetrato… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Interestingly, parents seem to explain the presence of a risk with two factors -parenting (or, more accurately -the lack of it) and specific child-related characteristics (e.g., attention-seeking or risk-taking behaviors). This finding aligns with previous studies that have found similar links between parental perceptions of sexual abuse risk (Collins 1995, Eelmaa 2021. Likewise, Byrne and others (2014) found that parents tend to think that their children are smarter than others while online, which in turn contributes to the increasing likelihood of underestimating some risky online behaviors.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Interestingly, parents seem to explain the presence of a risk with two factors -parenting (or, more accurately -the lack of it) and specific child-related characteristics (e.g., attention-seeking or risk-taking behaviors). This finding aligns with previous studies that have found similar links between parental perceptions of sexual abuse risk (Collins 1995, Eelmaa 2021. Likewise, Byrne and others (2014) found that parents tend to think that their children are smarter than others while online, which in turn contributes to the increasing likelihood of underestimating some risky online behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with prior studies, the data indicated that regardless of being aware of different OSRs, parents tend to believe that their children are less likely to encounter such risks (Byrne et al 2014, Eelmaa 2021, Sukk and Soo 2018, Symons 2017. Interestingly, parents seem to explain the presence of a risk with two factors -parenting (or, more accurately -the lack of it) and specific child-related characteristics (e.g., attention-seeking or risk-taking behaviors).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A considerable body of research is yet to be done on the influence of parents on rape myth acceptance, especially in the Indian setting. Despite the fact that previous studies have examined the concept of rape myth acceptance and its effects on diverse demographic groups (Das & Bhattacharjee, 2022) and cultural settings, parental viewpoints on child sexual abuse (Eelmaa, 2021), less research has been done on the precise relationship between parental beliefs, attitudes and the acceptance of rape myths. Nevertheless, this research is crucial because it addresses a significant gap in our understanding of how the acceptance of rape myths contributes to parents' beliefs and attitudes.…”
Section: The Current Studymentioning
confidence: 99%